A EFEKTIVITAS DAN KONTRIBUSI RETRIBUSI PELAYANAN PASAR TERHADAP PENERIMAAN RETRIBUSI DAERAH DI KABUPATEN BERAU - Drajat, Dandy Ahmad (ECO-BUILD, 2017)
The purpose of this research is to know the level of effectiveness and contribution of acceptance of Retribution of Market Service to the acceptance of Regional Retribution in Berau District in 2008 until 2014. Analyzer used to test the hypothesis include: Effectiveness Ratio and Contribution Ratio. The results showed that the effectiveness of Market Service Levy collections during 2008 to 2014 "Very Effective" average achievement of 103.78% per year, this means the hypothesis is rejected. As if seen from the contribution, the second hypothesis that the researcher proposed was also rejected, because based on the results of the research note that the average acceptance of Retribution of Market Service to the acceptance of Regional Levies in 2008 s / d 2014.